Multiple contemporary arterial dissection in Ehlers-Danlos syndrome type IV - Anna Rocci; Enrico Paganelli; Angelo Rossetti; Carla Marcato; Davide Martorana; Maria Ilaria Tassoni; Roberto Quintavalla (Italian Journal of Medicine, 2015)
We report a case of multiple spontaneous arteries dissection in a 52-year-old female; the patient had a relevant family history of vascular complications and typical features so we hypothesized vascular Ehlers-Danlos syndrome (EDS) that was confirmed by genetic analysis of COL3A1 gene. We adopted a conservative approach: the patient was treated with heparin in the acute phase followed by aspirin and then celiprolol was started on the basis of a recent trial that demonstrates a reduction in arterial events in EDS patient treated. A careful follow-up was done with Doppler ultrasound and computed tomography scan, as non-invasive diagnostic techniques are preferred in these patients, and no other vascular symptomatic events have occurred. We tested all living relatives: half of them had COL3A1 mutation, they were referred to another center specialized in rare diseases and EDS for long-term follow-up and genetic counseling. This case demonstrates as a careful evaluation of clinical signs, clinical history of the patient and his family has allowed a definitive diagnosis, proper management of the patient during the acute event and in terms of prophylaxis of recurrence.